Periodontitis and malignancy: a growing concern - Chandran, Nanditha; Melath, Anil; Kayakool, Subair; Gopinath, Gokul; Shahzadi, Hamda (International Journal of Research in Medical Sciences, 2025)
Periodontitis is an inflammatory disease affecting the supporting structures of the tooth resulting in tooth mobility and tooth loss. Periodontitis has been consistently associated with a higher risk for head and neck cancer. Possible mechanisms include the chronic inflammatory nature of the disease, epigenetic damage to the epithelial cells by periodontal pathogens and dysbiosis. The present review focuses on various pathways of spread of head and neck cancers and the role of various periodontal pathogens in initiating this carcinogenesis.